Inclusion of citizens in the food waste reduction missions in Europe and US – a comparison - Kunttu, Leena; Kalliomäki, Helka; Kalliokoski, Johanna; Kuusisto, Jari (International Society for Professional Innovation Management ISPIM, 2024)
As the ever-increasing problems related to the food waste have both environmental and socio-economic problems, the decreasing the food waste has widely acknowledged as a grand societal challenge globally. As the major producer of the food waste, private households play a central role in this. The national innovation systems and policy makers are developing systemic tools to answer to this challenge by driving innovation across multiple sectors and actors and enable bottom-up learning and experimentation with the households. Reducing food waste programs in different parts of the world can be seen as missions where governments and policy makers aim at improving the consumers' behaviour related to food waste. The purpose of this paper is to we compare the missions that aim at reducing food waste in Europe and USA and understand how different groups of citizens have been taken into account in these missions.
Keywords: mission; grant societal challenges; food waste; fi=Aluetiede|en=Regional Studies|